Mesoscale combustor-powered thermoelectric generator: Experimental optimization and evaluation metrics. (15th August 2020) - Li, Guoneng; Zheng, Youqu; Guo, Wenwen; Zhu, Dongya; Tang, Yuanjun
Highlights: A mesoscale combustor-powered TEG was designed and optimized. The contradiction between Bi2 Te3 availability and low-temperature limit was solved. An electric power of 30.7 W was generated with an overall efficiency of 3.21%. The ( EFS / ef TE, max ) at P in metrics was proposed to evaluate different TEGs. The obtained metrics (75.9%/4.23%) at 957 W is higher than previous reports. Abstract: The recent development of potable power sources is of considerable interest. A mesoscale combustor-powered thermoelectric generator integrated with a mesoscale stagnation-point reverse-flow combustor and a built-in heat exchanger was designed and optimized in this work to augment electric power and overall efficiency. The mesoscale combustor can run at a volumetric heat load of 72 MW/m 3 . The thickness of heat spreader, input power, equivalent ratio, fuel types, and heat exchanger channel types were explored to optimize the system performance. The optimized electric power of 30.7 W obtained at an overall efficiency of 3.21% was larger than the previous record of 18.1 W at an overall efficiency of 3.01% in 2015. The proposed thermoelectric generator, which was conducted with 13.2 kg of methane, reached an energy density of 300 Wh/kg. The novel design provided a concrete way to solve the contradiction between the availability of Bi2 Te3 -based thermoelectric module and its relatively low working temperature. Additionally, a new metrics, which is defined as ( EFS / ef TE, max ) at P in, was firstly proposed to evaluate various thermoelectric generators, in which different thermoelectric materials, combustion types, and input powers could be involved. The proposed metrics correlates the overall, running thermoelectric, maximum thermoelectric, combustion (reaction), and heat collection efficiencies under different input powers. The power of this metrics was comprehensively discussed by deducing the running thermoelectric efficiencies of various previous works and presenting the performance comparisons of different previous thermoelectric generators. The obtained metrics, that is, (75.9%/4.23%) at 957 W in this work was higher than those in previous studies.